2020
DOI: 10.1038/s41467-020-16470-8
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide substance P regulates aldosterone secretion in human adrenals

Abstract: Aldosterone, produced by the adrenals and under the control of plasma angiotensin and potassium levels, regulates hydromineral homeostasis and blood pressure. Here we report that the neuropeptide substance P (SP) released by intraadrenal nerve fibres, stimulates aldosterone secretion via binding to neurokinin type 1 receptors (NK1R) expressed by aldosterone-producing adrenocortical cells. The action of SP is mediated by the extracellular signal-regulated kinase pathway and involves upregulation of steroidogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…KaNDy Therapeutics demonstrated that elinzanetant is effective in the treatment of VMS in a phase II trial [80]. The potent action of elinzanetant on NK1 receptors is posited to bring some benefit with regard to peripheral flushing and sleep in VMS [80], whereas the alternate effects of NK1 antagonists on centrally mediated emesis and addiction circuits [26,27], gastrointestinal pharmacology [28], and the hypothalamic-pituitary-adrenal axis [81] is of unknown consequence in menopausal women. Additional clinical testing will further characterize the NK1R/NK3R pharmacology of elinzanetant.…”
Section: Expert Opinionmentioning
confidence: 99%
“…KaNDy Therapeutics demonstrated that elinzanetant is effective in the treatment of VMS in a phase II trial [80]. The potent action of elinzanetant on NK1 receptors is posited to bring some benefit with regard to peripheral flushing and sleep in VMS [80], whereas the alternate effects of NK1 antagonists on centrally mediated emesis and addiction circuits [26,27], gastrointestinal pharmacology [28], and the hypothalamic-pituitary-adrenal axis [81] is of unknown consequence in menopausal women. Additional clinical testing will further characterize the NK1R/NK3R pharmacology of elinzanetant.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Continuous monitoring of cortisol levels, one of the indicators of chronic stress, the potential cause of various diseases, can greatly help to prevent chronic diseases. [148,162] To continuously monitor cortisol secreted from the adrenal glands in terms of stress, Sunwoo et al demonstrated that a flexible probe inserted into the adrenal gland could measure electrophysiological signals correlated with cellular activity (Figure 8b). [9] This developed probe was fabricated by patterning metal electrodes of Au and Cr on a polyimide (PI) substrate, which has been shown to be biocompatible.…”
Section: Functional E-drugs For Chronic Diseasesmentioning
confidence: 99%
“…Aldosterone biosynthesis in the ZG is physiologically regulated by Angiotensin II (Ang II), potassium (K + ), and at a lesser extent by the AdrenoCorticoTropic Hormone (ACTH). Other bioactive compounds (serotonin, leptin, endothelin, nitric oxide, catecholamines, atrial natriuretic peptide, neuropeptide substance P) released by adipocytes, mast cells, chromaffin cells, or nerve ending located close to ZG cells were also shown to stimulate aldosterone secretion [ 3 , 4 ]. Stimulation of the Renin–Angiotensin System (RAS) is initiated by increased sympathetic activity, reduced perfusion pressure in the renal afferent arterioles, or decreased sodium content in the macula densa of the renal distal tubules, which lead to the release of renin from juxtaglomerular cells.…”
Section: Mineralocorticoid Signaling Pathwaymentioning
confidence: 99%